DETECTION OF CORROSIVES AND INHALANTS UNRAVELS THE TALE OF VIOLENCE AGAINST WOMEN AND CHILD: FORENSIC CASE REPORT (Journal of Forensic Medicine & Toxicology, 2024)
Violence against women (VAW) is basically violation of critical global human rights which is a manifestation of discrimination against women. The deeply rooted patriarchal attitude condones this violence. The change required in attitude and perception towards women on gender equality is an arduous process and is still going to take time to change (WHO 2020).The current case report discussed two cases which emphasized mainly upon crime against women, including violence related to dowry which leads to suicide in one case, and a second case of kidnapping and sexual assault of a ten-year-old girl. In all the two cases household corrosive substance and inhalants were used to commit crime. Qualitative analysis of substances was done by using latest techniques including Fourier Transform Infrared Spectroscopy (FTIR), Headspace-Gas chromatography - Mass spectroscopy (HS-GC-MS). The paper discusses various aspects of qualitative identification, and intricacies involved in interpretation of result especially
Keywords: Violence; Corrosive; Inhalants; Chromatography; Spectroscopy